Behavioural ecology of a tea pest, Andraca bipunctata (Lepidoptera: Bombycidae), in the Sub-Himalayan climate of Darjeeling (India) - Ghorai, Narayan; Raut, Srimanta; Bhattacharyya, Asit (Biological Letters, 2011)
The summer generation (G1) of Andraca bipunctata Walker in Darjeeling was confined to May-December and the winter generation (G2) extended from August to June. One female laid on average 480 and 526 eggs in G1 and G2, respectively. Larvae fed on Camellia sinensis and C. assamica leaves. Duration of 1st, 2nd, 3rd, 4th and 5th instars were 7, 7, 6, 6 and 6 days in G1, and 20, 20, 24, 72 and 33 days in G2, respectively. Temperature seems to greatly influence the duration of its life stages. A fungus (Paecilomyces tenuipes Samson), garden lizard Calotes versicolor (Daudin), and several bird species (Stachyris nigriceps Blyth, Spelaeornis caudatus (Blyth) and Dendrocitta frontalis Horsefield) were found effective in reducing the population of A. bipunctata.